2017
DOI: 10.1002/glia.23289
|View full text |Cite
|
Sign up to set email alerts
|

Affected astrocytes in the spinal cord of the leukodystrophy vanishing white matter

Abstract: Leukodystrophies are often devastating diseases, presented with progressive clinical signs as spasticity, ataxia and cognitive decline, and lack proper treatment options. New therapy strategies for leukodystrophies mostly focus on oligodendrocyte replacement to rescue lack of myelin in the brain, even though disease pathology also often involves other glial cells and the spinal cord. In this study we investigated spinal cord pathology in a mouse model for Vanishing White Matter disease (VWM) and show that astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 57 publications
6
14
0
Order By: Relevance
“…8,11 The presented astrocytes derived from mouse and human iPSCs recapitulate earlier findings in mouse and human, such as increased proliferation, morphological abnormalities, and induction of decreased oligodendrocyte maturation. 8,11 The presented astrocytes derived from mouse and human iPSCs recapitulate earlier findings in mouse and human, such as increased proliferation, morphological abnormalities, and induction of decreased oligodendrocyte maturation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…8,11 The presented astrocytes derived from mouse and human iPSCs recapitulate earlier findings in mouse and human, such as increased proliferation, morphological abnormalities, and induction of decreased oligodendrocyte maturation. 8,11 The presented astrocytes derived from mouse and human iPSCs recapitulate earlier findings in mouse and human, such as increased proliferation, morphological abnormalities, and induction of decreased oligodendrocyte maturation.…”
Section: Discussionsupporting
confidence: 74%
“…8,11 The presented astrocytes derived from mouse and human iPSCs recapitulate earlier findings in mouse and human, such as increased proliferation, morphological abnormalities, and induction of decreased oligodendrocyte maturation. 8,11 To our knowledge, we are the first to present VWM iPSC models involving subtype-specific astrocytes. 8,11 To our knowledge, we are the first to present VWM iPSC models involving subtype-specific astrocytes.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Astrocytes play a central role in pathology in VWM (Bugiani et al, 2011;Leferink et al, 2017). The presented astrocytes derived from miPSCs and hiPSCs recapitulate earlier findings in mouse and human, such as increased proliferation, morphological abnormalities and induction of decreased OPC maturation (Bugiani et al, 2011;Dooves et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…This is especially clear in Vanishing White Matter (VWM), one of the more prevalent leukodystrophies, which is caused by mutations in the EIF2B1-5 genes and for which no treatment is available (Van der Knaap, 2016). Previous studies showed that white matter astrocytes are selectively affected in VWM, while grey matter astrocytes are spared (Bugiani et al, 2011;Bugiani et al, 2013;Dooves et al, 2016;Leferink et al, 2017). These findings indicate that it is essential to generate iPSC models for disease-related astrocyte subtypes.…”
Section: Introductionmentioning
confidence: 94%